ANALISIS PENGELOLAAN KEUANGAN PADA UMKM DI PASAR TRADISIONAL: (STUDI KASUS PADA PASAR TRADISIONAL DI DESA LARANGAN, SIDOARJO) - Aulia, Septiana Winda; Junjunan, Mochammad Ilyas; Febry Fabian Susanto (Universitas Prof.Hazairin,SH Bengkulu, 2025)
This aim of this studyiss to analyze financial management, specifically focusing on planning, recording, reporting, and financial control according applied to small businesses in traditional markets, particularly at the Larangan Traditional Market in Sidoarjo. The research utilizes a qualitative method with a case study approach and is categorized as field research. Data collection techniques include interviews, observations, and documentation. The subjects of this study are business operators in the traditional market of Larangan Village, Sidoarjo. The results indicate that a significant number of business operators in the Larangan Traditional Market still face challenges in financial management. Their financial recording and budgeting practices are relatively simple. This is because MSME operators do not require the processes of planning, recording, reporting, and control according to the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM), as their primary goal is to run their businesses to meet daily needs. This research is expected to support the government in developing more targeted training materials to enhance the understanding and motivation of MSME in managing their businesses.